Pengujian Perangkat Lunak untuk Penulisan Hasil Belajar pada Pelajar SMK pada Pelaksanaan Kurikulum 2013 - Saifudin, Aries; Desyani, Teti; Amsyah, Antomy; Jalil, Abdul; Luthtiansyah, Luthtiansyah; Ardiansyah, M. Virzy (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
This review meant to portray execution of learning results report composing of professional understudies on Educational plan 2013 utilizing the web-based report composing programming. This examination was elucidating exploratory review, which was essential for the exploration improvement by utilizing Sharma's model. Information gathered by perception and poll. Members in this review included 9 both public and private professional school in Exceptional Locale, including the VPs of educational plan, study hall educators, and data innovation experts from school members. The outcomes look that 56% of respondents expressed that the created programming has great quality and the leftover 44% of source person expressed that the product created has mid-range quality. A few respondents ideas for enhancements to the product, to be specific (1) the requirement for synchronization of the framework with the freshest unofficial laws (2) improvement of the culmination of data inside the framework; (3) the requirement for participation with the branch of instruction / other related organizations; (4) impediment the power of the understudies. In view of these ideas have been led further developing the framework with the goal that the product was prepared for using to help professional instructors in Indonesia to set up the learning results writes about Education plan  program 2013.